NLP: En New Age-teknik som management fashion - Magaard, Tina (Religionsvidenskabeligt Tidsskrift, 2015)
Management techniques originating in the New Age movement have become increasingly popular in private as well as public organiza-tions in Denmark. Based on a combination of desk research and qualitative interviews, this article proposes an interdisciplinary study of those techniques as management fashions, investigating whether NLP (Neuro-Linguistic Programming) has been evicted or absorbed by concurrent techniques such as enneagram and coaching. It argues for the cross-fertilizing effects of including management theories in religious studies, when searching to grasp the presence of New Age-related phenomena in organizations.